Control and eradication of a disease: the history of poliomyelitis and its actors (Tempo e Argumento, 2010)
The main objective of this paper is to promote the collection of oral memory of Poliomyelitis. This research was undertaken under the project 'The history of polio and its eradication in Brazil’, which consists of 31 interviews with people who acted as public administrators, epidemiologists, scientists, technicians and doctors, involved in several ways and different trajectories in the elimination of polio in Brazil and in the world.
Keywords: polio; polio history; collection of oral history; public health